Photocatalytic activity of hierarchical Ti–Zr–ZSM-5 catalysts from attapulgite by MRS. Issue 2 (4th May 2019) - Li, Hong-Ji; Zhang, Jian-Min; Yang, Jing; Song, Jing-Hua; Yu, Chen-Hui
Abstract : Hierarchical architectures of titanium (Ti)–zirconium (Zr)–zeolite Socony Mobile–Five (ZSM-5) nanocrystalline aggregates were synthesized in a microwave-assisted rapid system. The micro–mesoporous structure and single-site photocatalytic activity of the nanocrystals were developed by using acidized attapulgite (microwave-treated acidized attapulgite) in the precursor solution. The morphology, crystallinity, surface area and porosity of the samples were characterized by Fourier transform infrared spectroscopy, X-ray diffraction, scanning electron microscopy, transmission electron microscopy and nitrogen gas (N2 ) adsorption–desorption. Results demonstrate that titanium–zirconium–ZSM-5 single-site heterogeneous catalysts persist on the typical framework of mordenite framework inverted structure and present a new spherical aggregate morphology made-up of hexagonal nanocrystals. The synthesis time required is reduced from 12 h to 180 min. The hierarchical nanocrystals have a Brunauer–Emmett–Teller surface area (349·51 m 2 /g) similar to and a mesopore volume larger than (0·23 cm 3 /g) those of commercial zeolites. The tetrahedrally coordinated metal oxide (titanium and zirconium) moieties were implanted and isolated in the silica matrices of micro–mesoporous ZSM-5 zeolite, which had a significant photocatalytic activity and reusability for degrading methylene blue dyeing wastewater. As a microreactor, the nanocrystals, with single-site photocatalytic activity, are worthy to be investigated further for potential applications in catalysis for dyeing and wastewater treatment.